Matching in the Dark? Inequalities in Student to Degree Match - Campbell, Stuart; Macmillan, Lindsey; Murphy, Richard; Wyness, Gill (Journal of Labor Economics, 2022)
This paper examines inequalities in the match between student and degree quality using linked administrative data from schools, universities, and tax authorities. We analyze two measures of match at the university subject level: undergraduate enrollment qualifications and graduate earnings. We find for both that disadvantaged students match to lower-quality degrees across the entire distribution of achievement in a setting with uniform fees and a generous financial aid system. While there are negligible gender gaps in academic match, high-attaining women systematically undermatch in terms of expected earnings, driven by subject choice. These inequalities in match are largest among the most undermatched.